THE INFLUENCE OF MARKET SEGMENTATION ON CUSTOMER DECISIONS IN CHOOSING BANK SYARIAH INDONESIA IN NORTH LUWU REGENCY - Sahrir, Sukmawati Sultan (Equilibrium : Jurnal Ilmiah Ekonomi, Manajemen dan Akuntansi, 2024)
AbstractThe Influence of Market Segmentation Based on Geography, Demographics, Psychographics, and Behavior on Customer Decision in Choosing Islamic Banks in North Luwu Regency" This study aims to determine whether Geographic, Demographic, Psychographic, and Behavioral segmentation influences customer decisions in choosing Islamic banks in North Luwu Regency. This study uses quantitative methods with a population of people in North Luwu Regency totaling 330,600 individuals, and a sample of 100 respondents using theSlovin formula, with data collection through distributing questionnaires. The research method used is multiple linear analysis with the assistance of SPSS version 26 software. The results show that first, the Geographic variable partially has a positive and significant effect on customer decisions in choosing Islamic banks in North Luwu Regency. Second, the Demographic variable partially has a positive and significant effect on customer decisions in choosing Islamic banks in North Luwu Regency. Third, the Psychographic variable has a positive and significant effect on customer decisions in choosing Islamic banks in North Luwu Regency. Fourth, the Behavioral variable has a positive and significant effect on customer decisions in choosing Islamic banks in North Luwu Regency. Fifth, Geographic, demographic, psychographic, and behavioral variables simultaneously have a significant effect on customer decisions in choosing Islamic banks in North Luwu Regency. The Adjusted R-square result is obtained at 0.823 or 82%. The remainder is explained by other variables that are not described.Keywords: Market Segmentation; Customer Decisions; Islamic Bank AbstrakPengaruh Segmentasi Pasar Berdasarkan Geografi, Demografi, Psikografi, dan Perilaku Terhadap Keputusan Nasabah dalam Memilih Bank Syariah di Kabupaten Luwu Utara" Penelitian ini bertujuan untuk mengetahui apakah segmentasi Geografi, Demografi, Psikografi, dan Perilaku berpengaruh terhadap keputusan nasabah dalam memilih bank syariah di Kabupaten Luwu Utara. Penelitian ini menggunakan metode kuantitatif dengan populasi masyarakat di Kabupaten Luwu Utara yang berjumlah 330.600 jiwa, dan sampel sebanyak 100 responden dengan menggunakan rumusSlovin, dengan pengumpulan data melalui penyebaran kuesioner. Metode penelitian yang digunakan adalah analisis linier berganda dengan bantuan software SPSS versi 26. Hasil penelitian menunjukkan bahwa pertama, variabel Geografis secara parsial berpengaruh positif dan signifikan terhadap keputusan nasabah dalam memilih bank syariah di Kabupaten Luwu Utara. Kedua, variabel Demografis secara parsial berpengaruh positif dan signifikan terhadap keputusan nasabah dalam memilih bank syariah di Kabupaten Luwu Utara. Ketiga, variabel Psikografis berpengaruh positif dan signifikan terhadap keputusan nasabah dalam memilih bank syariah di Kabupaten Luwu Utara. Keempat, variabel Perilaku berpengaruh positif dan signifikan terhadap keputusan nasabah dalam memilih bank syariah di Kabupaten Luwu Utara. Kelima, Variabel geografis, demografis, psikografis, dan perilaku secara simultan berpengaruh signifikan terhadap keputusan nasabah dalam memilih bank syariah di Kabupaten Luwu Utara. Hasil Adjusted R-square diperoleh sebesar 0,823 atau 82%. Sisanya dijelaskan oleh variabel lain yang tidak dijelaskan.Kata kunci: Segmentasi Pasar; Keputusan Nasabah; Bank Syariah